Unleashing the genome of Brassica rapa - Haibao eTang; Eric eLyons (Frontiers in Plant Science, 2012)
The completion and release of the Brassica rapa genome is of great benefit to researchers of the Brassicas, Arabidopsis, and genome evolution. While its lineage is closely related to the model organism Arabidopsis thaliana, the Brassicas experienced a whole genome triplication subsequent to their divergence. This event contemporaneously created three copies of its ancestral genome, which had diploidized through the process of homeologous gene loss known as fractionation. By the fractionation of homeologous gene content and genetic regulatory binding sites, Brassica’s genome is well placed to use comparative genomic techniques to identify syntenic regions, homeologous gene duplications, and putative regulatory sequences. Here, we use the comparative genomics platform CoGe to perform several different genomic analyses with which to study structural changes of its genome and dynamics of various genetic elements. Starting with whole genome comparisons, the Brassica paleohexaploidy is characterized, syntenic regions with Arabidopsis thaliana are identified, and the TOC1 gene in the circadian rhythm pathway from Arabidopsis thaliana is used to find duplicated orthologs in Brassica rapa. These TOC1 genes are further analyzed to identify conserved noncoding sequences that contain cis-acting regulatory elements and promoter sequences previously implicated in circadian rhythmicity. Each 'cookbook style' analysis includes a step-by-step walkthrough with links to CoGe to quickly reproduce each step of the analytical process.